Regulation and Function of the PD-L1 Checkpoint - Sun, Chong; Mezzadra, Riccardo; Schumacher, Ton N (Immunity (Cambridge, Mass.), 2018)
Expression of programmed death-ligand 1 (PD-L1) is frequently observed in human cancers. Binding of PD-L1 to its receptor PD-1 on activated T cells inhibits anti-tumor immunity by counteracting T cell-activating signals. Antibody-based PD-1-PD-L1 inhibitors can induce durable tumor remissions in patients with diverse advanced cancers, and thus expression of PD-L1 on tumor cells and other cells in the tumor microenviroment is of major clinical relevance. Here we review the roles of the PD-1-PD-L1 axis in cancer, focusing on recent findings on the mechanisms that regulate PD-L1 expression at the transcriptional, posttranscriptional, and protein level. We place this knowledge in the context of observations in the clinic and discuss how it may inform the design of more precise and effective cancer immune checkpoint therapies.